The impact of working from home on employee performance during COVID-19 epidemic - Didinova, Iryna (2021)
The novel coronavirus pandemic, currently rushing around the world, has forced governments to impose movement restrictions on their citizens. Authorities implemented local or national lock-downs, work-place risk controls, and business closures. Many companies have followed government regulation to work from home. Given this new situation, organisations across the world are now seeking “the new normal” in which remote working is the standard. In this instance, research on revealed employee performance while working from home is currently more scarce than ever. This study analyzes how working from home impacts employee performance. Data used in the study are internal individual-level anonymized data about employees of real Prague insurance firm in years 2018-2020. The model was fitted using the 2SLS estimator due to the possible endogeneity of Home office participation, caused by self-selection. As a result of such analysis, no impact of working from home on employee performance was found. This result is valid for narrowly defined type of employee: middle office and back office of insurance and banking industry. Moreover, it provides an useful insight even for many similar types of administrative positions.